2004
DOI: 10.1117/12.548883
|View full text |Cite
|
Sign up to set email alerts
|

Performance improvements for VOx microbolometer FPAs

Abstract: Raytheon is producing high-quality 320 x 240 microbolometer FPAs with 25 µm pitch pixels. The 320 x 240 FPAs have a sensitivity that is comparable to microbolometer FPAs with 50 µm pixels. Typical NETD values for these FPAs are <50mK with an f/1 aperture and operating at 30 Hz frame rates. Pixel operability is greater than 99.9% on most FPAs, and uncorrected responsivity nonuniformity is less than 4% (sigma/mean). These 25 µm microbolometer detectors also have a relatively fast thermal time constant of approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 6 publications
(6 reference statements)
0
15
0
Order By: Relevance
“…Conventional single-level infrared bolometer arrays with small pixel pitches typically have a fill factor between 60% and 70% (b = 0.6 to 0.7) [10,11,18]. Two-layer bolometer designs (umbrella designs) have been reported that reach pixel fill factors of up to 90% (b = 0.9) [12,18].…”
Section: Analysis Of Bolometer and System Design Features That Can Dementioning
confidence: 98%
See 3 more Smart Citations
“…Conventional single-level infrared bolometer arrays with small pixel pitches typically have a fill factor between 60% and 70% (b = 0.6 to 0.7) [10,11,18]. Two-layer bolometer designs (umbrella designs) have been reported that reach pixel fill factors of up to 90% (b = 0.9) [12,18].…”
Section: Analysis Of Bolometer and System Design Features That Can Dementioning
confidence: 98%
“…Thus, a high fraction of the incident infrared radiation at a specific wavelength k is absorbed in the bolometer membrane [9]. For a targeted wavelength interval of 8-14 lm, the distance between the bolometer membrane and the mirror on the substrate is typically about 2-2.5 lm [9,12]. In such a bolometer design only the upper surface of the bolometer membrane is radiating.…”
Section: Calculational Model For the Noise Equivalent Temperature Difmentioning
confidence: 99%
See 2 more Smart Citations
“…To reduce the noise and enlarge the sensitivity, the heat transfer between the VO x film and the substrate of the cavity should be as low as possible, therefore conventional bolometers operate with vacuum levels \0.01 mbar (Murphy et al 2004). This presents a challenge to the packaging technology since gas leakage usually exists over time.…”
Section: Introductionmentioning
confidence: 99%